5 - Understanding Gender-based Violence: Evidence from Kilimanjaro Assessment of Rombo and Moshi Rural - Jane Saffitz, (African Sociological Review, 2010)
This paper presents findings from an empirical study on the prevalence and beliefs surrounding gender-based violence (gBv) in the Kilimanjaro region. The analysis and ensuing discussion is the result of a representative sample of adults (n=384) surveyed in two districts, Rombo and Moshi Rural, in Kilimanjaro, tanzania. In contrast to previous research of a similar nature, which has focused primarily on the frequency of violence, this study devotes significant atten- tion discerning the level of social acceptability among its victims and perpetrators situated in a legal and cultural framework. I find that alcohol consumption and the number of deceased children within a household have a direct correlation to incidences of gBv while an indi- vidual’s level of education and degree of financial independence are inversely related to rates of violence. The influence of bride price and polygamy is inconclusive. finally, I find that although a portion of the population believes women should have decision-making capabilities, patri- archal institutions and a culture that relegates women as inferior have a significant impact on individual attitudes among men and women to preserve the status quo. These results suggest a greater need to promote a culture of egalitarianism in a sensitive and relevant manner.